In vivo effects of cefazolin, daptomycin, and nafcillin in experimental endocarditis with a methicillin-susceptible staphylococcus aureus strain showing an Inoculum effect against cefazolin (2013)
Several reports have implicated the inoculum effect that some strains of type A beta-lactamase (Bla)-producing, methicillin-susceptible Staphylococcus aureus (MSSA) show against cefazolin as the cause for clinical failures in certain serious deep-seated infections. Here, using a previously reported MSSA strain displaying this phenotype (TX0117), we obtained a Bla-cured derivative (TX0117c) with a combination of novobiocin and high temperature. Both isolates were then used in a rat endocarditis model and treated with cefazolin, nafcillin, and daptomycin, given to simulate human dosing. Animals were treated for 3 days and either sacrificed at 24 h after the last antibiotic dose (standard group) or left untreated for an additional 3 days (relapse group). With TX0117 in the standard treatment group, daptomycin and nafcillin were both significantly better than cefazolin in reducing CFU/g of vegetations, achieving mean log10 reductions compared to levels in untreated rats of 7.1, 5.3, and 1.8, respectively (cefazolin versus daptomycin, P < 0.0001; cefazolin versus nafcillin, P = 0.005; daptomycin versus nafcillin, P = 0.053). In addition, cefazolin was significantly more effective in reducing vegetation titers of TX0117c than of TX0117 (mean log10 reduction of 1.4 versus 5.5, respectively; P = 0.0001). Similar results were observed with animals in the relapse group. Thus, these data show that there can be an in vivo consequence of the in vitro inoculum effect that some MSSA strains display against cefazolin and indicate a specific role for Bla production using a Bla-cured derivative strain against which cefazolin regained both in vitro and in vivo activity.